Analisis Ketidakseimbangan Beban Transformator Distribusi Terhadap Arus Netral Di PT. PLN (Persero) ULP Abepura Penyulang Melati - Dultudes Mangopo; Ekawati Margaretha Ohee; Rosalina Revassy; Aris Sampe; Luther Pagiling; Yuni Aryani Koedoes (Jurnal Fokus Elektroda : Energi Listrik, Telekomunikasi, Komputer, Elektronika dan Kendali), 2024)
One of the consequences of load imbalance is the flow of current in the neutral wire. The current flowing on the neutral wire will cause heat, so indirectly, the consequences of load imbalance contribute to losses for PLN as a producer of electricity. The purpose of this study is to the percentage of transformer load imbalance, the percentage of losses due to neutral current in the transformer neutral conductor. The method used in this research is collecting distribution transformer load data on the Melati extent. From the results of the data analysis, it is obtained that the largest percentage of load imbalance occurs in transformer AB-225 with a loading percentage of 64.95% LWBP and 65.74% WBP. Based on the results of the analysis the total percentage of losses due to the neutral current on the neutral conductor of the transformer is 7.89% and 9.76% LWBP and WBP, respectively.